The mediating role of organizational learning in the relationship between organizational commitment and lecturer innovative behavior - Wati Wahyuni; Bedjo Sutanto; Supadi Supadi (IICET (Indonesian Institute for Counseling, Education and Therapy), 2021)
Innovation is one of the basic assets needed for organizations to survive in a competitive environment. Organizations such as higher education also need strong innovation in order to continue to compete and produce high-quality graduates. This study aims to analyze the factors that influence the innovative behavior of lecturers, especially based on organizational learning and organizational commitment. The research was conducted at STIK-PTIK with a sample of 108 lecturers who were taken randomly. Data collection using a questionnaire with Likert scale 1-5 and data analysis using path analysis. The results showed that organizational learning and organizational commitment had a positive direct influence on the innovative behavior of lecturers. Organizational learning is also known to have a positive direct influence on the organizational commitment of lecturers. Other findings indicate that organizational commitment plays a role in the influence of organizational learning on innovative behavior. Based on these results, then factors organizational learning and organizational commitment need to be improved in order to increase the innovative behavior of lecturers.